2020
DOI: 10.1186/s12889-020-09268-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of fall-related injuries: a retrospective study

Abstract: Background: Fall-related injuries are important public health problem worldwide. We aimed to describe the epidemiological and clinical characteristics of fall-related injuries in a level 1 trauma center. Method: A retrospective analysis of Qatar Trauma Registry data was conducted on patients admitted for fall-related injuries between 2010 and 2017. Comparative analyses of data by gender, age-groups and height of falls were performed to describe the epidemiological and clinical characteristics of patients, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…The AIS describes the severity of injuries at different body regions; the score ranges from 1 to 6. AIS scores of three most severely injured body regions were squared and added together to estimate the ISS, which provided an overall score for polytrauma (ISS 1–8 is minor injury, 9–15 is moderate, 16–24 is serious, 50–74 is critical, and 75 is non-survivable) [ 18 ]. The trauma registry prospectively records the fall data (fall from height and fall of heavy objects) using codes by International classification of diseases, 10th revision (ICD-10), which classified unintentional falls into 20 subcategories (W00-W19) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The AIS describes the severity of injuries at different body regions; the score ranges from 1 to 6. AIS scores of three most severely injured body regions were squared and added together to estimate the ISS, which provided an overall score for polytrauma (ISS 1–8 is minor injury, 9–15 is moderate, 16–24 is serious, 50–74 is critical, and 75 is non-survivable) [ 18 ]. The trauma registry prospectively records the fall data (fall from height and fall of heavy objects) using codes by International classification of diseases, 10th revision (ICD-10), which classified unintentional falls into 20 subcategories (W00-W19) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“… 6 It has been reported that IDD is associated with an aberrant cell-mediated response to structural failure, such as endplate fracture or vertebral burst fracture. 7 , 8 However, whether a single impact injury of the endplate without structural disruption, which is commonly seen in the clinic, 9 is sufficient to initiate IDD is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that, among survivors of fall injuries, falling distance was associated with the number of lower-limb fractures, the severity of spinal vertebral fractures, and the duration of ICU and hospital stays. Mekkodathil et al reported in their study of 4,040 patients with fall injury that 29% of patients with fall injury had a spinal injury, and the spine was one of the most common injury sites in fall injury [ 13 ]. These findings indicated that falls especially from high places resulted in vertebral fracture severity, more lower-limb fractures, and longer ICU and hospital stays.…”
Section: Discussionmentioning
confidence: 99%